Inequalities and Resistances in The Organization of Marginalized Festive Practices - Procópio da Silva, Nathália Brunet; Fantinel, Letícia Dias (Organizações & Sociedade, 2021)
This article is based on the understanding of festivals as organizations and events that are multiform and establish mediations with society (Amaral, 1998a; Davel, 2016). Based on a multi-political perspective, our objective was to reflect on the social production of inequalities and forms of resistance in the organization of the congo capixaba festival, in the state of Espírito Santo. Our theoretical reflections were grounded in Certeau’s (Certeau, 1985, 2008, 2012; Certeau, Giard, & Mayol, 2003), Hall’s (2003, 2011) and Sansone’s (2004) discussions and reflections regarding contemporary black culture. Our empirical field of investigation was the Carnaval de Congo de Máscaras [Congo Masquerade Carnival], in Roda D’água, where we employed the ethnographic method as a data production and interpretation strategy. Our findings indicate the existence of “non-places” as products of historically produced conditions of social marginality, as well as an ethnic-racial invisibility reinforced in the festival’s organizational context. These non-places operate in the religious, touristic, and cultural macropolitical fields. On the other hand, we highlight how the subjects of such conditions deal with them by employing certain micropolitical tactics, which figure prominently in their everyday lives, and articulate themselves around a sense of tradition and belonging.